2019
DOI: 10.4250/jcvi.2019.27.e31
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Enhanced Ultrasound Perfusion Imaging in Skeletal Muscle

Abstract: The ability to accurately evaluate skeletal muscle microvascular blood flow has broad clinical applications for understanding the regulation of skeletal muscle perfusion in health and disease states. Contrast-enhanced ultrasound (CEU) perfusion imaging, a technique originally developed to evaluate myocardial perfusion, is one of many techniques that have been applied to evaluate skeletal muscle perfusion. Among the advantages of CEU perfusion imaging of skeletal muscle is that it is rapid, safe and performed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
0
9
0
1
Order By: Relevance
“…US is useful in evaluating soft tissues and is almost comparable to MRI in detecting periprosthetic collections (16). Its value in assessing muscle edema and vascularization (37,38) has never been evaluated in the context of PJI, and evaluation of deep alterations can be challenging. CT, however, was shown by Cyteval et al (17) to be sensitive and specific when at least one soft-tissue abnormality (joint distention, fluid-filled bursae, or fluid collections) was used to diagnose PJI.…”
Section: Interobserver Agreementmentioning
confidence: 99%
“…US is useful in evaluating soft tissues and is almost comparable to MRI in detecting periprosthetic collections (16). Its value in assessing muscle edema and vascularization (37,38) has never been evaluated in the context of PJI, and evaluation of deep alterations can be challenging. CT, however, was shown by Cyteval et al (17) to be sensitive and specific when at least one soft-tissue abnormality (joint distention, fluid-filled bursae, or fluid collections) was used to diagnose PJI.…”
Section: Interobserver Agreementmentioning
confidence: 99%
“…Conventional techniques to evaluate PAD are of limited ability to estimate diffuse or small vessel disease, or microvascular dysfunction, which are fundamental aspects of the pathophysiology of PAD. 23 Clinical studies have shown that perfusion imaging can evaluate PAD severity. 24 In a study of patients with PAD, perfusion deficits in the calf muscles and disease severity were determined by contrast‐enhanced ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“… 25 A previous study showed that patients with PAD with intermittent claudication compared with controls had lower peak exercise perfusion and lower limb perfusion. 23 Moreover, patients with PAD and diabetes were found to have poor tissue perfusion and flow impairment attributable to microvascular dysfunction. Perfusion imaging by contrast‐enhanced ultrasound showed patients with diabetes with microvascular complications had reduced capillary volume recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die muskuläre Perfusion unterliegt daher einer strengen Regulierung, die für die gesamte kardiometabolische Gesundheit lebensnotwendig ist. Der Blutfluss variiert dabei von 20 % des Herzzeitvolumens (HZV) in Ruhe bis zu 80 % während körperlicher Anstrengung, wobei Höchstwerte von bis zu 50-60 ml/ 100g/ min erreicht werden können [20][21][22]. Zusammengefasst wurde gezeigt, dass die Skelettperfusion in der Lage ist, sich um das 100-fache, ausgehend von Ruhebedingungen, zu erschöpfender, zyklischer Muskelarbeit zu steigern [21,23].…”
Section: Physiologieunclassified